The health of Arab-Americans living in the United States: a systematic review of the literature - Galea Sandro; El-Sayed Abdulrahman M (BMC, 2009)
Abstract Background Despite substantial attention paid to Arab-Americans (AAs) in the media and in public discourse, there is limited research about the health of AAs in the United States (US) in the public health literature. This review aims to synthesize the extant peer-reviewed literature concerned with the health of AAs living in the US. Methods We summarize existing research on the prevalence, relative burden compared to other ethnic and racial groups, and determinants of diseases within each morbidity cluster among AAs living in the US. Results Available evidence suggests that the health of AAs may differ from that of other ethnic and racial groups in the US, and that exposures specific to this ethnic group, such as immigration, acculturation, and discrimination may be important in the etiology of several diseases among AAs. Conclusion Given the growth of this ethnic group and its marginalization in the current sociopolitical climate, more research about the health of AAs in the US seems warranted. We summarize relevant methodological concerns and suggest avenues for future research.